Effects of high heat shocks on seed germination in Turkish Red Pine (Pinus brutia Ten.) populations - Sezgin AYAN; Cihan ERKAN; Orhan GÜLSEVEN; Şeyma Selin AKIN; Ergin YILMAZ; Esra Nurten YER ÇELİK (Turkish Journal of Forestry, 2019)
The aim of this study was determine the germination ability and viability of Turkish red pine seeds representing different populations at different altitudes and that are exposure to different heat shock applications with different duration. For this purpose, Turkish red pine seeds which obtained from 14 different populations was exposed to 4 different heat shocks (70, 90, 110 and 130 ºC) during 1 and 5 minutes. It was once again proven with this study that seeds of Turkish red pine are resistant to heat shock. As a result of the study, it was determined that the seeds of four different breeding zones and 14 populations between 60 and 925 meters altitude were able to maintain their viability in high theat shocks up to 130 °C. Also, Turkish red pine seeds that were applied high heat shock at 130 ºC during 1 minute had showed maximum germination ability.